2002
DOI: 10.1182/blood.v99.10.3830
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of human cytomegalovirus peptide–specific cytotoxic T-lymphocyte responses by interferon-γ–enzyme-linked immunospot assay and flow cytometry in healthy individuals and in patients after allogeneic stem cell transplantation

Abstract: Reconstitution of human cytomegalovirus (HCMV)-specific cytotoxic T lymphocytes (CTLs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 35 publications
4
104
2
1
Order By: Relevance
“…Indeed the CMV-specific CD4 þ and CD8 þ T-cell responses both represented 10% of their respective T-cell repertoire. Such extreme immunodominance of CMV in the post transplant period has been observed in other studies 28 and may reflect the observation of CMV latency and reactivation in myeloid DCs. 32 The CMV-specific CD4 þ T-cell immune response is unusual in that the great majority of the population is comprised of cytotoxic CD4 cells, a minority population within the CD4 þ T-cell repertoire.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed the CMV-specific CD4 þ and CD8 þ T-cell responses both represented 10% of their respective T-cell repertoire. Such extreme immunodominance of CMV in the post transplant period has been observed in other studies 28 and may reflect the observation of CMV latency and reactivation in myeloid DCs. 32 The CMV-specific CD4 þ T-cell immune response is unusual in that the great majority of the population is comprised of cytotoxic CD4 cells, a minority population within the CD4 þ T-cell repertoire.…”
Section: Discussionmentioning
confidence: 74%
“…In HSCT, several studies have demonstrated the importance of both the CD4 þ and CD8 þ CMV-specific T cells in protection from CMV reactivation. 27,28 More recently, Lilleri proposed that an absolute CD4 and CD8 count of 1 and 3 cells/ml, respectively, may be valuable in protection from recurrent CMV reactivation in young HSCT patients. 14 Our data shows a clear association between reconstitution of the CD4 þ CMV-specific T-cell immune response within the first 50 days and protection against CMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The MUC1 protein sequence was screened with HLA class I binding algorithms provided by the SYFPEITHI software as described earlier 15,16, and new MUC1 peptides binding to HLA-A*6801, HLA-B*0702 and HLA-B*4402 were predicted. The peptides (Table 2) were synthesized using standard fluorenylmethoxycarbonyl chemistry on an automated peptide synthesizer (432A; Applied Biosystems, Weiterstadt, Germany).…”
Section: Peptidesmentioning
confidence: 99%
“…Analysis of T cell response in transplanted patients who did not develop HCMV disease showed contrasting results. Indeed, high frequencies of IE1-but not pp65-speciWc CD8+ T cells were found protective in one case [29] whereas, rising numbers of pp65-speciWc T cells correlated with immune reconstitution in another case [30]. Interestingly, all patients protected by IE1-specifc T cells were HCMV-seropositive before transplantation suggesting that viral reactivation was responsible for expansion of CTL against IE1 which is produced in large amounts in the IE phase.…”
Section: Role Of Cross-presentation To Bypass Viral Subversion and Inmentioning
confidence: 98%